Revealing the ventral amygdalofugal pathway of the human limbic system using high spatial resolution diffusion tensor tractography - Kamali, Arash; Sair, Haris I.; Blitz, Ari M.; Riascos, Roy F.; Mirbagheri, Saeedeh; Keser, Zafer; Hasan, Khader M. (Brain Structure and Function, 2016)
The amygdala is known to have a role in core processes regulated by the limbic system such as motivation, memory, emotion, social behavior, self-awareness as well as certain primitive instincts. Several functional studies have investigated some of these brain tasks of the human limbic system. However, the underlying neuronal fiber connectivity of the amygdalo-diencephalon, as part of the limbic system, has not been delineated separately by prior diffusion-weighted imaging studies. The ability to trace the underlying fiber connections individually will be helpful in understanding the neurophysiology of these tracts in different functions. To date, few diffusion-weighted studies have focused on the amygdala, yet the fine connections of the amygdala, hypothalamus, septum or other adjacent limbic structures have yet to be elucidated by diffusion-weighted tractography studies. We therefore aimed to further investigate these fine neuronal connections using fiber tractography and high spatial resolution diffusion tensor imaging on 3T on 15 healthy right-handed male human subjects (age range 24–37 years). The ventral amygdalofugal pathway, anterior commissure and stria terminalis are the three main efferent pathways of the amygdala. We delineated the detailed trajectories of the ventral amygdalofugal tract, anterior commissure and their connections bilaterally in 15 normal adult human brains. Using a high-resolution diffusion tensor tractography technique, for the first time, we were able to demonstrate the trajectory of amygdalofugal tract and its connections to the hypothalamic and septal nuclei. We further revealed, for the first time, the close relationship of the amygdalofugal tract and anterior commissure with the fornix, stria terminalis and uncinate fasciculus bilaterally in 15 healthy adult human brains.